STRATEGI PEMENANGAN ASEP WAHYUWIJAYA PADA PEMILIHAN UMUM LEGISLATIF TAHUN 2024 - Awaludin, Iksan; Anas, Azwar (Program Studi Komunikasi dan Penyiaran Islam, 2023)
Elections are always an interesting issue for all levels of society, especially regarding the political strategies of each candidate aiming for leadership positions. The purpose of this study is to understand and explain the political strategies employed by Asep Wahyuwijaya to secure a seat in the Indonesian House of Representatives (DPR-RI) in the 2024 General Election. The research method used is qualitative, with purposive sampling focusing on selected informants who are rich in cases for an in-depth study. The findings of this study show that the winning strategy used includes offensive, defensive strategies, and Peter Schroder’s strategies of Cooperate, Pavlov, and Mistrust. In the offensive strategy, Asep Wahyuwijaya employs various approaches, including forming volunteer teams, switching political parties, political collaboration, placing billboards, and maximizing mass media and social media. The conclusion is that Asep Wahyuwijaya's political strategy in the 2024 legislative election combines both offensive and defensive approaches effectively to increase his chances of victory. Through forming volunteer teams, switching parties, and collaborating with other candidates, Asep Wahyuwijaya is able to tackle challenges such as money politics and skepticism about political loyalty. His political education approach and transparent communication successfully reduce dependence on money politics and contribute to creating a healthier and more integral political climate in Bogor Regency